Neonatal gastric perforation: a case report: Perforacija želodca v neonatalnem obdobju - Sukič, Klavdija; Miksić , Mirjana; Jagrič, Tomaž; Potrč, Stojan (Acta Medico-Biotechnica, 2021)
Purpose: Neonatal gastric perforation is a rare life-threatening clinical condition. It is usually handled in a neonatal intensive care unit setting. Many theories have been proposed to explain the etiology and pathogenesis of gastric perforation in the neonatal period, but in many cases they remain unknown. Prematurity and low birth weight are known as risk factors.Case report: We report a 4-day-old male infant that was delivered by emergency Cesarean section because of placental abruption at 29-weeks gestational age. On the 4th day, the baby developed rapid abdominal distension with rapid progression to shock. Abdominal radiography showed free intra-peritoneal air. An emergency laparotomy revealed a perforation in the smaller curvature of the stomach that was sutured after excision of the surrounding ischemic stomach wall.Conclusion: Gastric perforation in a newborn infant represents an immediate surgical emergency with high mortality. Early diagnosis and early intervention may improve the prognosis associated with vigorous supportive measures.
Keywords: gastric perforation; premature neonate; pneumoperitoneum; gastrectomy